Development characteristics of coal fines and its influence on output in Shizhuang Coalbed Methane Block of Qinshui Basin - Wenlong HAN; Yanbin WANG; Li WANG; Shihu ZHAO (Meikuang Anquan, 2023)
Identifying the characteristics of coal fine development and production can guide the exploration and development of coalbed methane (CBM). In this paper, drilling coring, logging information, drainage and production data, and coal fine samples from CBM wells were collected in Shizhuang area, Qinshui Basin, China. Based on logging interpretation, laser particle size analysis and mass fraction testing, the development characteristics of coal fine and its impact on production were systematically analyzed. The results show that the primary coal fine in the study area can be divided into five areas: complex coal fine development, coal fine at the bottom of the coal seam, no coal fine, less coal fine, and coal fine at the top and bottom of the coal seam. The output coal fine particle size distribution ranges from 0.4 μm to 3 300 μm, and the concentrated coal fine mass fraction ranges from 0 to 0.5. The development characteristics of coal fine affect the initial pulverized production time of CBM wells. The complex area generally produces coal fine for the first time before the occurrence of gas. The undeveloped areas and less developed areas generally produce coal fine for the first time after the occurrence of gas. Affected by the development of coal fine near the wellbore, the coal fine produced in the drainage and depressurization stage is mainly composed of medium and coarse particles, and the coal fine mass fraction is not high. Affected by the drainage intensity and the development characteristics of coal fine, the coal fine produced in the production and deflation stage is dominated by medium and fine particles, and the coal fine mass fraction is high and fluctuates greatly. In the stable gas production stage, CBM wells mainly produce primary coal fine and secondary coal fine produced by fracturing engineering in distal fractures. The coal fine particles and the mass fraction fluctuation are small. The output of coal fine in the gas production decay stage is small.